Managing responsible antimicrobial use: perspectives across the healthcare system. (July 2017) - Dyar, O.J.; Tebano, G.; Pulcini, C.; ,
Abstract: Background: Healthcare systems consist of building blocks. Shaping how these building blocks function and interact can promote responsible antimicrobial use, and this represents an important opportunity for managers at different points within healthcare systems to act upon. Aims: To review real-world examples of how healthcare systems can promote responsible antimicrobial use, focusing on the role of governance and managers. Sources: We searched and reviewed existing literature and official documents, which mostly focused on antibiotics. We also drew on the diverse experiences of the ESGAP (the ESCMID (European Society of Clinical Microbiology and Infectious Diseases) Study Group for Antimicrobial stewardshiP) network. Content: First, we explored at the institution level the implementation of antimicrobial stewardship programmes, the need to embrace multidisciplinary approaches, the benefits of engaging with social sciences experts, and the role of governance and leadership. We look beyond individual institutions and highlight the urgent need for workforce capacity estimates for antimicrobial stewardship activities, how antimicrobial stewardship efforts can connect to form networks, and the importance of governance and regulation at national and international levels. Implications: Managers in the healthcare system are in a strong position to look beyond individual prescriptions and to recognize the many ways in which different healthcare system building blocks can contribute to responsible use of antimicrobials. At the institution level this can be achieved by implementing antimicrobial stewardship programmes, ensuring they are adequately resourced, and driving buy-in across clinical leadership. At regional and national levels this includes facilitating the sharing of experiences and resources between institutions, and developing the standards and regulations needed to support responsible antimicrobial use.